Umbilical Endometriosis, a Rare Clinical Entity: Case Report and Management in Port-Harcourt, Nigeria, Africa - Iwo-Amah R. S.; Jumbo A. I.; Altraide B. O. A.; Okah K.; Lebara L. B.; Amachree P. T.; Briggs N. N.; Wadi I.; Ndii L. D.; Weje F. C. (Medicine and Medical Research: New Perspectives Vol. 3, 2024)
Endometriosis is the presence of endometrial tissue outside the lining of the uterine cavity. It is a benign gynaecological disorder affecting about 5% of reproductive-age women. The aetiology is uncertain, but certain theories are postulated, like retrograde menstrual regurgitation of viable endometrial glands and tissue along the fallopian tubes and subsequent implantation on the pelvic peritoneal surfaces. These cells respond to hormones in a cyclical manner. Surgical procedures that breach the endometrium can inoculate other parts of the pelvis with endometrial tissue, there is also haematological spread. Cyclical bleeding from these deposits leads to inflammation, fibrosis, and adhesions. Umbilical endometriosis is the presence of an endometrial gland and stroma in the umbilicus. It is a rare site of occurrence. It is usually preceded by a history of pelvic surgery, as was found in this patient. The management usually involves a multidisciplinary team comprising the gynaecologist, the plastic surgeon, the colorectal surgeon, Fertility and Pain management teams. This was the case of a 33-year-old nullipara, who had abdominal myomectomy 5 years prior to presentation. She noticed bleeding and pain from her umbilicus one year ago. Bleeding was cyclical, associated with her menses, and was bright red in colour. The umbilicus eventually produced a tender-feeling, hyperpigmented exophytic mass. There was a laparotomy, intraperitoneal adhesiolysis, and total removal of the umbilical tumour. She experienced no pain during her first menstruation following surgery, and the repaired umbilical location was free of haemorrhage. She will be sent to the fertility team when she is prepared to begin a family. The significance of this study is that every clinician, especially gynaecologists should have a high index of suspicion of endometriosis when a young woman presents with bleeding from unusual sites.